2023
DOI: 10.1021/acs.jcim.3c01496
|View full text |Cite
|
Sign up to set email alerts
|

Deep Generative Models in De Novo Drug Molecule Generation

Chao Pang,
Jianbo Qiao,
Xiangxiang Zeng
et al.

Abstract: The discovery of new drugs has important implications for human health. Traditional methods for drug discovery rely on experiments to optimize the structure of lead molecules, which are timeconsuming and high-cost. Recently, artificial intelligence has exhibited promising and efficient performance for drug-like molecule generation. In particular, deep generative models achieve great success in de novo generation of drug-like molecules with desired properties, showing massive potential for novel drug discovery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 146 publications
(254 reference statements)
0
11
0
Order By: Relevance
“…10 However, previous RL models based on "atom and bond" growth often produce molecules with unrealistic structures that lack synthesizability and reasonable drug-like properties and therefore are often unable to verify their biological activity. 11 To overcome these limitations, researchers have put forward fragment-based algorithms. 12−14 Following the methodology proposed in ref 14, we have developed a fragment-by-fragment RL forward synthesis algorithm for generating molecules based on the lead compound and reaction templates.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 However, previous RL models based on "atom and bond" growth often produce molecules with unrealistic structures that lack synthesizability and reasonable drug-like properties and therefore are often unable to verify their biological activity. 11 To overcome these limitations, researchers have put forward fragment-based algorithms. 12−14 Following the methodology proposed in ref 14, we have developed a fragment-by-fragment RL forward synthesis algorithm for generating molecules based on the lead compound and reaction templates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to its remarkable capacity for exploration and learning, RL has gained popularity in the field of multiobjective optimization for drug molecular design . However, previous RL models based on “atom and bond” growth often produce molecules with unrealistic structures that lack synthesizability and reasonable drug-like properties and therefore are often unable to verify their biological activity . To overcome these limitations, researchers have put forward fragment-based algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Attributed to the success of syntactic pattern recognition in language modelling tasks, early molecular generative models are designed on the basis of SMILES, a line notation that describes chemical structures using ASCII strings. However, SMILES representation is limited by its intrinsic instability in describing molecular structural information, as structurally similar molecules can result in dissimilar SMILES strings [4].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ProGen, a large-scale protein language model, generates protein sequences with predictable functions across diverse protein families, also aiding in the exploration of protein space [7]. Similarly, in the realm of small molecule design, there has been a proliferation of published generative language models utilizing string-based molecule representations, garnering considerable attention [8]. As for RNA research, while pre-trained language models have demonstrated efficacy in RNA function and structure prediction [9], the generation of RNA sequences remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%